Written and Submitted to the Nahdlatul Ulama University of Blitar as One of the Requirements for Completing the Bachelor Program in English Education Department - anto, Eko Yuli; Saifudin, Ahmad; Widiarini, Widiarini; Makrifah, Istina Atul (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This research aims to develop an interactive PowerPoint (PPT) as a learning media to enhance students’ writing skills, specifically in composing procedure texts for 10th grade students at MA Ma’arif NU Blitar. The study employed the Research and Development (R&D) method, using the ADDIE model which consists of five phases: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, questionnaires, pre-tests, and post-tests. The findings revealed that the developed interactive PPT significantly improved students’ writing performance. This improvement was evident in the increase of average scores from pre-test to post-test, and supported by positive responses from students regarding the clarity, engagement, and effectiveness of the media. Media validation results also showed a high level of feasibility and appropriateness. The interactive PPT includes animations, quizzes, and hyperlinks to foster active learning. In conclusion, this interactive PPT proved to be a feasible and effective media to support writing instruction and enhance students’ engagement and achievement.